Pengoperasian Purse Seine Pada KMN. Enterprise di Perairan Selat Makassar - Tomasila, Leopold A; Sinau, Silvester; Rusdianto; Tuhumena, Lolita (Cenderawasih University, 2023)
The fishing ground is the waters of the Makassar Strait. The activity starts on January 21st 2023 until April 9th, 2023. Unknowledge about fishing techniques with purse seine catch and fishing catch tools with various and function. The objective of that final on board training purse seining gration to identify the facilities and infrastructure used in carrying out operational activities purse this and can identify the catch. The results of observations during the implementation of the final on board raining show that work procedures within purse seining gration of FB Enterprise, in the Makassar Strait consist of 2 main activity stages namely setting and hauling. Based on the results of observations, it can be concluded that the work procedure for on board fish handling starts from preparation, fish loading , sorting, washing fish in baskets, placing fish in pans, storing fish in the ABF hold at 180 By using freon, after that the fish will be packaged when the fish has frozen. The facilities and infrastructure used for handling are: gloves, basketball, pan, plastic pe and clean water